ON PREPARATION OF COMPETITIVE SPECIALISTS-FINANCES UNDER THE REQUIREMENT OF THE MODERN LABOR MARKET - Ковальчук, В.; Ковальчук H. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article examines the requirements of the modern labor market for the professional training of financiers, the essence and structure of the professional orientation of the individual, reveals the purpose and principles of professional training. The essence of the concept of "professionalism" as the result of organizational and purposeful professional activity and the main directions of professionalization is considered. The result of professional growth of the personality of the future specialist and the development of his professional abilities is the professional competence that a student acquires during his studies at the university. The necessity of training of competitive and competent specialists is determined; the classification structure of the professional competence of a specialist is considered. Professional competence is a measure and the main criterion of professional preparedness and the ability of the subject to perform tasks and duties in accordance with the position he occupies. The competence approach is considered as one of the priority directions of the modernization of education in Ukraine which becomes important as it translates the process of accumulation of normatively defined knowledge, skills and abilities into the plane of formation and development of students’ ability to practically act and apply creatively the acquired knowledge and experience in different situations. The article analyzes the essence and content of professional competence and examines different approaches to the classification of competencies. Also, the article reveals the concept and structure of "key competencies". The groups of key competencies are characterized: general sciences, and instrumental, socio-personal and general cultural. It is proved that the formation of the professional competence of students is carried out through the content of vocational education, in the process of mastering disciplines distributed in different training cycles, outlines the general tendencies of becoming a personality of a student-financier as a future specialist. The educational qualification characteristics of future specialists and their significance for the formation of OPP and the development of disciplines in accordance with the curriculum of the higher educational institutions are researched. The level of professional activity according to the classifier of professions and the correspondence of educational and professional programs of preparation of different levels of specialists are described. The authors came to the conclusion that it is necessary to model the professional skills of a future specialist who are part of a holistic pedagogical process at the university